Corporate finance text and Philippine cases - Ybanez, Roy C.; Ilano, Alberto R.; Echanis, Erlinda S.; Cayanan, Arthur S.; Santos-Valderrama, Helena Agnes; Florendo, Joselito G.; Borja, Daniel Vincent H.; Lee, Gavin C.; Bautista, Carlos C.; Salazar, Dani Rose (Development Center for Finance, College of Business Administration, University of the Philippines, 2009)
Volume 1 provides an extensive treatment of working capital management, and includes chapters of tools, which are essential to financial management: financial statement analysis, financial forecasting, and the mathematics of discounting.